Impact of electrical energy consumption and occupancy in university building - Razak I.S.A.; Tan C.S. (Alpha Publishers, 2023)
In Malaysian universities, energy wastage tends to occur mainly due to inefficient use of energy and lack of information among institutions occupancy. Most of the energy consumption is contributed from the operation of HVAC and lighting system. However, the energy consumption remains the same during final exam week and semester break even though the occupancy in the college is low. It is mainly due to the lack of ignorance and awareness in managing the use of electrical energy in dwellings. Connected with the hike in electricity bills to the University, therefore it is important that swift actions can be taken to reduce the bills via energy efficiency measures. This paper highlights preliminary results of the electrical energy consumption for 3 blocks in College of Engineering (COE), Universiti Tenaga Nasional (UNITEN). This paper also identifies potential areas of energy saving in those blocks. Finally, suggestions on the ways to improve electrical energy usage in those buildings. This study indicates that by implementing no cost initiatives into COE buildings, the university can potentially save up to 11.9% of its monthly electrical bills by switching off lightings for one hour. 2020 Alpha Publishers.